Molecular and morphological evidence support a new species of Rosaceae Prunus subg. Cerasus from Wuyishan National Park, southeast China - Yi, Xiangui; Dong, Jingjing; Chen, Jie; Zhou, Huajin; Wu, Tong; Gao, Shucheng; Chen, Xiangzhen; LI, Meng; Wang, Xianrong (PhytoKeys, 2024)
Prunus tongmuensis , a new species of cherry blossom, is described and illustrated from Wuyishan National Park, southeast China. This species is characterized by its tubular to nearly bottle-shaped receptacles and dark purple drupes. It can be distinguished from other wild cherry trees by its flowers and leaves, reddish brown young leaves, presence of 1–2 glands at the base of leaves, petioles densely covered with yellowish brown villi, longer pedicels (0.6–2.5 cm), villous pistil, and dark purple drupes. In the present study, we conducted a comprehensive morphological study based on specimens of the new species and its morphologically close species, field observations, and examination of pollen morphology. In addition, our phylogenetic analysis based on the complete plastid genome sequences further confirms the status of the new species and indicates that it is closely related to Prunus clarofolia , however, it notably differs in leaf shape, size, petiole villus color, gland location, timing of flower and leaf openings, and reflexed or spread sepals, as well as drupe color.